2003
DOI: 10.1385/bter:96:1-3:133
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Ca Ionophore A23187 on Zinc-Induced Apoptosis in C6 Glioma Cells

Abstract: Zinc ions are essential, but at elevated concentrations, they also have toxic effects on mammalian cells. Zinc plays a crucial role in cell proliferation and differentiation and it even protects cells against apoptosis caused by various reagents. On the other hand, zinc at high concentrations causes cell death that was characterized as apoptotic by internucleosomal DNA fragmentation, formation of apoptotic bodies, and breakdown of the mitochondrial membrane potential. In the present work, a clone of rat C6 gli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…MVso btained from different stimulations (starvation or LPS/Ca ionophore) demonstrated similarendotoxin levels. This finding togetherw ith the fact thatt he wash medium obtained from the MVs production hadnoeffect on cellviability,and previous study whichs howedt hat Ca ionophore does not leadt o apoptosis (32), confirm thatthe resultspresentedhereinare induced by MVs and are notrelated to otherparameters,such as LPS or Ca ionophore residue. Recent studies that demonstrated that (i) MPsinduce dysfunction and apoptosis in other cell systems (33)(34)(35);(ii) apoptotic cells becomeprocoagulant (36); and (iii) detached EC indicatear apidM Ps formation (37), further supportour findings.…”
Section: Discussionsupporting
confidence: 85%
“…MVso btained from different stimulations (starvation or LPS/Ca ionophore) demonstrated similarendotoxin levels. This finding togetherw ith the fact thatt he wash medium obtained from the MVs production hadnoeffect on cellviability,and previous study whichs howedt hat Ca ionophore does not leadt o apoptosis (32), confirm thatthe resultspresentedhereinare induced by MVs and are notrelated to otherparameters,such as LPS or Ca ionophore residue. Recent studies that demonstrated that (i) MPsinduce dysfunction and apoptosis in other cell systems (33)(34)(35);(ii) apoptotic cells becomeprocoagulant (36); and (iii) detached EC indicatear apidM Ps formation (37), further supportour findings.…”
Section: Discussionsupporting
confidence: 85%
“…The Ca 2+ ionophore A23187 for example has high affinity for a wide variety of cations, raising the question as to whether accepted Ca 2+ ionophore responses are primarily attributable to Ca 2+ or Zn 2+ . [79][80][81] Treatment of platelets with Py or Cq results in increases in [Zn 2+ ] i , with Cq producing a greater response. 79 [Zn 2+ ] i increases correlate with platelet activation.…”
Section: Release Of Zn 2+ Upon Platelet Degranulationmentioning
confidence: 99%
“…RT-CES system can provide the information about cell proliferation after treatment with chemicals [24]. Briefly, HLE B-3 cells were plated into an E-plate at a density of 8.0×10 3 cells per well and grown overnight, and then the cells were treated with ZnCl 2 (i.e., 0, 5, 10, 20, 40, and 80 μg/mL) [25]. For the monitoring of cytotoxicity using RT-CES system, once cells were added to the sensor wells, the sensor devices were placed into the incubator and the real-time cell index (CI) data acquisition was initiated by the RT-CES analyzer.…”
Section: Assessment Of Cytotoxicitymentioning
confidence: 99%